Instrument to assess the nursing care product: development and content validation - Danielle Fabiana Cucolo; Márcia Galan Perroca (Universidade de São Paulo, 2015)
AbstractObjectives: develop and validate the content of a tool about nursing care production.Method: the data were collected between 2011 and 2013, based on focus groups, the application of semistructured questionnaires (prototype test) and the Delphi technique. The focus groups were used to produce the instrument items and held at three hospitals in the interior of the State of São Paulo, involving 20 nurses. A panel of 10 experts evaluated the instrument.Results: after two phases of the Delphi technique, the tool consisted of eight items. The content validity index of the scale corresponded to ≥0.9 and the content validity of the items ranged between 0.8 and 1.0, indicating the maintenance of the structure and content. The assertion on the applicability in daily nursing practice showed a content validity index of the scale equal to 0.8.Conclusion: this study permitted the development and content validation of scale on nursing care production, equipping the nurses in their management practice.